Correlation between serum bilirubin, blood uric acid, and C-reactive protein and the severity of chronic obstructive pulmonary disease - Tingting Zhao; Tian Lv (BMC, 2024)
Abstract Objective To explore the correlation between serum bilirubin, blood uric acid, and C-reactive protein (CRP) and the severity of chronic obstructive pulmonary disease (COPD). Methods: Patients with COPD who were admitted to our hospital between March 2020 and March 2023 were retrospectively studied. Based on whether their condition progressed to the acute exacerbation stage, they were divided into an exacerbation group (100 cases) and a stability group (100 cases). The clinical data from both groups were analysed to assess the correlations between serum bilirubin, blood uric acid, CRP, and the severity of COPD. Results: Univariate analysis indicated significant differences in the neutrophil-to-lymphocyte ratio (t = 5.678, P < 0.05), α-hydroxybutyrate dehydrogenase (t = 5.862, P < 0.05), total bilirubin (t = 4.341, P < 0.05), direct bilirubin (t = 5.342, P < 0.05), indirect bilirubin (t = 5.452, P < 0.05), blood uric acid (t = 4.698, P < 0.05), and CRP (t = 4.892, P < 0.05) between the two groups. Multivariate analysis revealed that total bilirubin, blood uric acid, and CRP were positively correlated with exacerbations of COPD (regression coefficients were 0.413, 0.354, and 0.356, respectively; P < 0.05). The evaluation of predictive value showed that the combined predictive value of these three indicators was the highest, with an AUC of 0.823 (95% CI: 0.754-0.911). Conclusion: Serum bilirubin, blood uric acid, and CRP levels are elevated in patients with acute exacerbations of COPD (AECOPD), showing good consistency in predicting the occurrence of AECOPD. The combined diagnostic value of these three indicators is greater than that of any single indicator, providing a reference for the early clinical prediction of AECOPD.